EVALUATING THE DYNAMIC ALIGNMENT OF HIGHER EDUCATION CURRICULUM WITH THE EVOLVING INDUSTRY LANDSCAPE: A MULTI-DIMENSIONAL ANALYSIS IN THECONTEXT OF INDONESIA - Yunus Kariyanto; Rina Asmaul; Zain Fuadi Muhammad Roziqi Fath; Ahmad Junaidi; Fatmawati Sabur (International Journal of Teaching and Learning, 2023)
This research delves into the complex relationship between higher education curricula and the rapidly evolving industry landscape within the Indonesian context. The study aims to assess the alignment of higher education curricula with the Industry's ever-changing demands. This alignment is of paramount importance as it directly influences the readiness of graduates to meet industry requirements. The research employs a multi-dimensional analysis framework, examining various factors influencing curriculum-industry alignment. These factors encompass curriculum content, industry expectations, and students' educational experiences. The study seeks to provide a holistic perspective on this alignment through an array of research methods, including curriculum analysis, surveys, and interviews with industry representatives and educators. The significance of this research is twofold. First, it contributes to the ongoing discourse on curriculum development within higher education, particularly within the Indonesian context. Second, it offers practical insights that can inform policy decisions and curriculum development in higher education institutions. Understanding the nuances of curriculum-industry alignment is crucial for preparing students effectively for the workforce and ensuring that the education system meets the evolving needs of the Industry. It is essential to acknowledge the limitations of this study, primarily related to the dynamic nature of industries and resource constraints. Nevertheless, the findings hold the potential to drive positive changes in the Indonesian higher education landscape, improving the responsiveness of curricula to the Industry and enhancing graduates' preparedness to face the challenges of a rapidly evolving job market. This research contributes to the broader conversation on curriculum alignment in higher education and offers a nuanced perspective within the Indonesian context.